Responses of runoff processes to vegetation dynamics during 1981–2010 in the Yarlung Zangbo River basin - Xiaowan Liu; Hui Lu; Kun Yang; Zongxue Xu; Jing Wang (Journal of Hydrology: Regional Studies, 2023)
Study region: The Yarlung Zangbo River basin (YRB), southwest China. Study focus: The vegetation conditions play a significant role in regulating river runoff under climate change. However, the effect of vegetation growth induced by climate change to runoff variation remains controversial as relevant studies are mainly focused on the influences of climate change to runoff variation and vegetation growth, respectively. In this study, the response of runoff generation to change of Leaf Area Index (LAI) inputs during 1981–2010 in YRB were explored by using the Variable Infiltration Capacity (VIC) model. New hydrological insights: The VIC model with dynamic LAI inputs performs better in the YRB, especially in the sub-basins with apparent peak clipping effect by LAI overestimation. The impact mechanism of how runoff variation is driven by LAI change in the meadow, tundra and cultivated vegetation cover is evapotranspiration-controlled by energy redistribution. However, the LAI changes in coniferous and broad-leaved forest cover affect the runoff generation mainly by redistributing energy-water to alter both evapotranspiration and surface soil moisture, so do the shrub and grassland during the growing season (Apr.∼Sep.). The results highlight implanting grassland would be efficient to reduce the flash flood runoff in a short term and balance groundwater runoff in a long run. The broad-leaved forest and coniferous forest with a longer growth cycle also play a main role in adjusting soil moisture.